EFEKTIVITAS POSITIONING JURUSAN MANAJEMEN DAN PENGARUHNYA TERHADAP TINGKAT KEPUASAN (SATISFACTIONS) JASA PELAYANAN (STUDI PADA PERGURUAN TINGGI SWASTA DI BANDARLAMPUNG) - Anuar Sanusi (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
This study aimed to determine the effectiveness of the formation of public perception management majors (positioning) through marketing strategies (product, promotion, place, price processes, people, services and the level of satisfaction). The results showed that the sequence of the highest variable shape their effectiveness is variable positioning process, variable service, variable space, variable pricing, promotion variable. Whereas variable ineffective cover variables, and variable products/ graduates. Variable attributes of brand loyalty in the visible frequency attributes in the sense that like the education (frequency) assessed by a variation less often quite high, but it will not reduce the assessment of the service received, for services provided management department meets department higher standards set. While others attribute to recommend to the comfort (comfortable) and preferences with services obtained got a pretty good assessment, while the other attributes that tend to get a very good assessment of the variation is almost the same. Attributes related to the service, is the most influential variable, and the most important factors to changes in loyalty management majors existence and Attributes related to the purchase of statistical models that also affect positively to the presence of the management department.Keywords : Positioning, Satisfaction, and Service